Construcción de un Robot Móvil Híbrido Omnidireccional - Ortega Noroña, Jhonny Fabricio (2017)
This section describes the construction and technical characteristics of actuators, sensors, control cards and special modules to be used in the omnidirectional hybrid scanning robot. The robot consists of an omnidirectional mobile platform and a robotic arm of 5 degrees of freedom with a clamp from which they can be used individually if required. The prototype is based on the image of an industrial robot known as the Kuka youBot, has as a characteristic of the maneuver on flat surfaces with unevenness of up to 10% of its horizontal length. The robot will be controlled wirelessly, with the direct manipulation of an operator that contours with the support of a friendly software, which allows an easy handling of the robot. The construction of the robot starts from a design previously mentioned, the hardware was realized in the impression in 3.D and the design was realized in the software Inventor. The respective functional tests will be carried out to verify the feasibility, in addition to the robot that serves as support in robotic applications in the field of research within the electronic engineering career.